With a Sensitive View to the Future - Hodgson, Gordon (ARCTIC, 1987)
. To celebrate the 40th anniversary of Arctic we solicited a number of papers. Some were papers of reminiscences; others were scholarly research/review papers. Thus we were fortunate to acquire reminiscences by a number of designers and leaders of the Arctic Institute over the years. . In addition to the reminiscent papers, we invited a number of scholars to prepare papers entitled "Forty years of ." to present reflections on a variety of northern topics. These papers were treated as regular manuscripts offered for publication in Arctic, with peer review, revisions and acceptance in the regular way. These papers make up the bulk of this anniversary issue. .